Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Low-velocity mudstone identification using well logs and prestack seismic data based on principal component analysis and multilayer perceptron - Mengyu Ren; Xuri Huang; Xiaoqing Cui; Ran Yang; Rong Zhang; Jingshi Liu; Chaoyi Niu (Journal of Applied Geophysics, 2026)

An inflammation-targeted hydrogel for the synergistic treatment of colorectal cancer and associated neuropsychiatric dysfunction - Keying Chen; Na Li; Anni Ren; Lingling Yang; Pei Xie; Yong Gao; Yanwu Li; Ying Tang; Rong Zhang; Huafeng Pan; Bangjiang Fang; Tongkai Chen; et al. (Chemical Engineering Journal, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Bioavailability, Migration, and Accumulation Characteristics of Heavy Metals in the Soil–Lotus Root System Adjacent to Highways - Qiang Hu; Rong-hua Qiu; Ren-chao Zhu; Manisha Parajuli; Si-jie Wen; Zi-yang Sun; Ai-hua Yu (International Journal of Environmental Research, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

Biotechnological upcycling of Laminaria japonica processing waste via Lactiplantibacillus plantarum fermentation: release and formation of antioxidant and tyrosinase-inhibitory compounds - Jing Wu; Haojie Lin; Rong Lin; Ritian Jin; Duo Liang; Zhongyang Ren; Wuyin Weng; Shen Yang (Food Chemistry, 2026)

Local electric field regulation induces specific catalysis to achieve efficient and selective sensing of methanol - Cundong Feng; Shizhu Ling; Rong Tan; Weian Du; Xueqin Ouyang; Jianjun Xiong; Yangfeng Li; Haoyang Ren; Yingpu Wang; Weifang Liao; Qian Xiao; Wentao Dong; et al. (Chemical Engineering Journal, 2026)

Spatial variations in soil carbon, nitrogen, and phosphorus stoichiometry across a northeast-southwest grassland transect in the monsoon-margin areas of China - Yuan Zhang; Na Rao; Bosen Yuan; Kai Wu; Xieping Xiang; Xumin Wei; Fangfang Xu; Jiusheng Ren; Yang Zhang; Ting Wu; Yun Zhang; Chao Huang; et al. (Journal of Soils and Sediments, 2026)

Assessing road network resilience to extreme rainstorms: A percolation and hydrodynamic approach - Fei Ma; Rong Fu; Wei Ren; Qing-Chang Lu; Qing Liu; Zhijie Yang; Zhong Ma (Transportation Research Part D: Transport and Environment, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

A high-performance polymer-modified bentonite liner for sustainable landfills: from systematic optimization to field validation - Wei Yang; Rong Zhou; Yifei He; Xueying Liu; Mengjian Ren; Anna Lushnikova (Journal of Environmental Management, 2026)

Soil texture modulates microbial responses to irrigation: Implications for nutrient cycling in arid agroecosystem - Kai Sun; Rong Yang; Zhuo Che; Wenzhi Zhao; Shujun Song; Haoqi Ren (Soil and Tillage Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Effect of long-term cultivation on ground arthropod diversity and network stability in desert agricultural ecosystems - Yongzhen Wang; Yilin Feng; Jialong Ren; Zhibin He; Jiliang Liu; Wenzhi Zhao; Rong Yang (Plant and Soil, 2026)

Increasing aridity reduces soil protist diversity and weakens its link to ecosystem functioning in grassland ecosystem, northern China - Rong Hao; Shuang Pang; Zonghao Hu; Wei Yang; Ximei Zhang; Haiyan Ren (Soil Ecology Letters, 2026)

Organic fertilization improves activities of phosphomonoesters hydrolase in rhizosphere to facilitate phosphorus acquisition in cucumber and accumulates organic phosphorus in soil - Bingshuang Wang; Yuan Wang; Xihe Zhang; Xiaodan Hu; Shujun Li; Yifei Sun; Yang Wang; Yan Sun; Ziwei Dai; Yunsheng Lou; Rong Li; Guohua Xu; et al. (Applied Soil Ecology, 2026)

Characteristics of VOCs emissions and environmental impact assessment of typical automobile manufacturing enterprises in Beijing, China - Yinquan Qiu; Xinyu Zhang; Rong Sun; Houjian Yang; Ming Liu; Lianhai Ren; Pan Wang (Air Quality, Atmosphere & Health, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

Effects of green manure mulching on the trophic structure of soil fauna in desert agricultural ecosystems of northwestern China - Yongzhen Wang; Zhibin He; Jiliang Liu; Yilin Feng; Jialong Ren; Wenzhi Zhao; Rong Yang (Applied Soil Ecology, 2026)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

ESG Scores and financial performance are making energy companies be in a dilemma: evidence from China - Fang-rong Ren; Hui-yi Chen; Xi-ting Yang; Xin-ge Guan; Xiao-yan Liu (Environment, Development and Sustainability, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

The late Eocene pine seed cones from Mangkang Basin, southeastern Xizang (Tibet) and their biogeographic significance - Xuan-Rong Yao; Yi Gao; Ren-Dan Yang; Jiang-Bo Meng; Shu-Feng Li; Tao Su (Palaeoworld, 2025)

Haloxylon ammodendron plantations: enhancing multi-trophic arthropod diversity and soil multifunctionality in arid deserts - Jialong Ren; Yongzhen Wang; Xiaogan Zhou; Wenzhi Zhao; Zhibin He; Rong Yang; Weidong Xin; Wei Ren; Chengchen Pan; Jiliang Liu (Journal of Environmental Management, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Application of biochar in saline soils enhances soil resilience and reduces greenhouse gas emissions in arid irrigation areas - Shixiong Ren; Jiawang Zhong; Kai Wang; Rong Liu; Hao Feng; Qin’ge Dong; Yuchen Yang (Soil and Tillage Research, 2025)

Mobile Genomic Island GEI-FN1A in Aeromonas salmonicida FN1 Contributes to the Spread of Antibiotic-Resistance Genes - Xinru Xie; Zhaorui Ren; Rong Wang; Kanglu Tian; Xindi Huang; Yang Lyu; Guangxiang Cao; Jiafang Fu (Current Microbiology, 2025)

Antibiotics shape the core microbial community distribution between floc and biofilm in an endogenous partial denitrification system: Insight from metabolic pathway - Kai-Yue Dong; Chao-Xi Yang; Jin-Luo Pang; Rong-Rong Chang; Ke-Yu Chen; Wei Yao; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Analysis of CO2 emission and energy consumption in CCUS for steel-chemical joint production - Huapeng Yang; Chao Feng; Tao Lin; Rong Zhu; Kai Dong; Guangsheng Wei; Mingwei Tu; Fuhai Liu; Ziheng Zhao; Xin Ren; Chunyang Wang (Journal of Environmental Management, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Recent advances and future research directions in the study of land-atmosphere interaction in northern China since the beginning of the 21st century - Qiang Zhang; Rong Wang; Ping Yue; Hongyu Li; Sheng Wang; Jian Zeng; Liang Zhang; Zesu Yang; Suping Wang; Jie Zhang; Liang Qiao; Hongli Zhang; et al. (Science China Earth Sciences, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Pyroptosis was suppressed by 20-hydroxyecdysone through Lin28b-mediated let-7d in vascular endothelial cells - Danli Chen; Jianjun Yang; Lingxuan Ren; Zihan Zheng; Zhen Jin; Jiazheng Wen; Jianyu He; Rongcheng Ding; Jianjiang Wang; Rong Lin; Qiang Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Effect of myosin-kappa carrageenan pickering emulsions on the quality of bighead carp surimi gels - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2025)

The reutilization of oolong tea waste: Synthesis of carbon dots and antibacterial mechanism against Staphylococcus aureus - Weian Ye; Shen Yang; Ritian Jin; Duo Liang; Zhongyang Ren; Rong Lin (Food Bioscience, 2025)

Effects of crop rotation on plant- and microbial-derived carbon within particulate and mineral fractions in paddy soils - Yalin Yu; Ningxuan Zhu; Ying Ren; Menghan Dong; Guofeng Sun; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Agriculture, Ecosystems & Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Bacillus subtilis fermented shrimp waste isolated peptide, PVQ9, and its antimicrobial mechanism on four Gram-positive foodborne bacteria - Weihong Tao; Wenjie Li; Jude Juventus Aweya; Rong Lin; Ritian Jin; Duo Liang; Zhongyang Ren; Shen Yang (Food Microbiology, 2025)

Novel Pickering emulsions using polysaccharide-myosin complexes: Effect of polysaccharide types - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

Navigating the trade-offs in crop production and soil quality through alternative cropping - Junlong Huang; Yi Xu; Mengsu Peng; Rong Jia; Juncong Chu; Amit Kumar; Changzhong Ren; Yadong Yang; Dongmei Wang; Xiaojun Wang; Zhaohai Zeng; Leanne Peixoto; et al. (Field Crops Research, 2024)

Effect of the spatial changes in engineering properties on municipal solid waste landfill slope stability - Rong Yang; Zengguang Xu; Junrui Chai; Cheng Cao; Jianxi Ren; Xiaoke Chang (Bulletin of Engineering Geology and the Environment, 2024)

Effect of whole-grain Tartary buckwheat fermentation with Monascus purpureus on the metabolic syndrome and intestinal flora in mice - Xin Yang; Rong Ren; Xiaoqin Lang; Xuanchen Li; Likang Qin; Haiying Zeng (Food Bioscience, 2024)

Quantitative analysis of the fluvial geomorphology and erosion on Hainan island: implications for the source-to-sink system in the NW South China Sea - Kai Qiu; Chao Lei; Chao Tang; Rong Yang; Sean Willett; Jianye Ren (Frontiers in Marine Science, 2024)
The sediment delivery from Hainan island into the NW South China Sea during the Quaternary is less well-defined. An investigation into the uplift, exhumation and fluvial geomorphology of the Hainan island is crucial for improving our understanding on the source-to-sink system in this region. In this study, we employed the digital elevation analysis, the stream power incision model and the cosmogenic nuclide isotope analysis to unravel how and why the Hainan island provide sediment to the NW South China Sea. The results show that the average HI values of the main catchments on the Hainan island are below 0.35, which indicates that the rivers on the Hainan island tend to be stable. After mapping the channel steepness index of the Hainan island, a high channel steepness index is constrained in the central and western Hainan island. The χ analysis shows minor variations in χ values across the Hainan island, except of the watershed between the Wanquanhe and Nandujiang rivers, as well as that between the Changhuajiang and Nandujiang rivers, which indicates the potential migration of the river watersheds here. In addition, we carried out the cosmogenic nuclide 10 Be analysis on the river sand from the Hainan island. The spatial distribution of 10 Be concentrations is identified to be high in the west and low in the east. The catchment-averaged erosion rates are quantified to be 35 m/Myr, 42.5 m/Myr and 69.9 m/Myr for the Changhuajiang, Wanquanhe and Lingshuihe catchments, respectively. We also estimated the sediment deliveries from the Changhuajiang, Wanquanhe and Lingshuihe catchments to the Qiongdongnan and Yinggehai Basins to be 0.46 Mt/yr, 0.45 Mt/yr and 0.21 Mt/yr, respectively. We compared our results of the fluvial geomorphology analysis and erosion rate estimates of the Hainan island with those of the Taiwan island. We concluded that the difference of the erosion pattern and river evolution of the Hainan and Taiwan islands may be associated with the variation of the tectonics. Our investigation on the evolution of the Hainan island will improve our understanding on the source-to-sink systems in the NW South China Sea.

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

A new simple index for characterizing the labile heavy metal concentration in soil by diffusive gradients in thin films technique - Yang-xiao-xiao Shi; Hai-rong Xu; Jia Shen; Lin-yu Guo; Jing Yan; Jun Jiang; Zhi-neng Hong; Ren-kou Xu (Environmental Pollution, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Nucleotide at position 66 of NS2A in Japanese encephalitis virus is associated with the virulence and proliferation of virus - Ning Tan; Chen Chen; Yang Ren; Rong Huang; Zhuang Zhu; Kui Xu; Xiaoyao Yang; Jian Yang; Lei Yuan (Virus Genes, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

N, N-bis (2-hydroxyethyl) malonamide based amidoxime functionalized polymer immobilized in biomembranes for highly selective adsorption of uranium(VI) - Yang Li; Ze-Yang Wang; Qi Ren; Feng Zhang; Xu-Xin Li; Qiang Wu; Rong Hua; Ze-Yi Yan; Yun Wang (Chemosphere, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

First report of fruit rot caused by Paramyrothecium foliicola on muskmelon in China - Jian Fei Huo; Yong Xia Ren; Yu Rong Yao; Hai Yan Ben; Xiu Yun Wen; Wen Lai Ren; Li Juan Yang; Wan Li Wang; Yong Juan Hao (Journal of Plant Pathology, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Role of quorum sensing-based regulation in development of anaerobic ammonium oxidation process - Jun-Hui Yang; Dong-Qi Huang; Yin-Ce Geng; Yi-Rong Ling; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2023)

Performance and Feasibility of Therapeutic Vibrating Mesh Nebulizer for Ventilation Lung Scan - Chih-Yung Chang; Bang-Hung Yang; Chien-Chih Ke; Jing-Long Hsu; Rong-Hong Jhou; Wen-Yi Chang; Nan-Jing Peng; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2022)

Concentrations, distribution, and risk assessment of endosulfan residues in the cotton fields of northern Xinjiang, China - Yang Zhang; Rong Guo; Yang Li; Mingyu Qin; Jingquan Zhu; Zhihong Ma; Yong Ren (Environmental Geochemistry and Health, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

The anticancer potential of the dietary polyphenol rutin: Current status, challenges, and perspectives - Arakkaveettil Kabeer Farha; Ren-You Gan; Hua-Bin Li; Ding-Tao Wu; Atanas G. Atanasov; Khalid Gul; Jia-Rong Zhang; Qiong-Qiong Yang; Harold Corke (Critical Reviews in Food Science and Nutrition, 2022)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease - Yu Chen; Li Ma; Shuo Yang; Jan-Karl Burkhardt; Junlin Lu; Xun Ye; Weijian Jiang; Zeguang Ren; Rong Wang; Xiaolin Chen; Yuanli Zhao (Translational Stroke Research, 2020)
The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up. The MTT defined as the blood transit time between the end of cervical portion (C1) and the C7 segment of ICA. The clinical prognosis was assessed with Matsushima grading system, moyamoya vessel reduction system, and modified Rankin Scale (mRS). The correlation between hemodynamic parameter and prognosis was analyzed. Subgroup analysis was conducted between different presentations and different ages. Fifty-one patients were identified and the mean imaging follow-up interval was 5.5 months. The ICA-MTT was increased after the combined revascularization ( P < 0.001) compared with contralateral ICA. Faster preoperative ICA-MTT was significantly associated with improved mRS in the ischemic group ( P = 0.05). The increased ICA-MTT was significantly associated with favorable neoangiogenesis ( P = 0.04), moyamoya vessel reduction (> 50%) ( P = 0.023), and improved mRS score ( P = 0.008). In subgroup analysis, the correlation in the ischemic subgroup and adult subgroup remained significant. In this cohort, the ICA-MTT increased after the combined EC-IC bypass, and there was a positive correlation between the increased blood transit time and favorable outcomes. Color-coding DSA proved to be useful as a quantitative and serial method to monitor postoperative courses after revascularization in MMD.

Complete genome sequence of Mycobacterium Mya-zh01, an endophytic bacterium, promotes plant growth and seed germination isolated from flower stalk of Doritaenopsis - Lijing Pan; Jimin Chen; Shumei Ren; Hanguo Shen; Biao Rong; Wen Liu; Zhenming Yang (Archives of Microbiology, 2020)

Decrypting the crosstalk of noncoding RNAs in the progression of IPF - Yujuan Wang; Han Xiao; Fenglian Zhao; Han Li; Rong Gao; Bingdi Yan; Jin Ren; Junling Yang (Molecular Biology Reports, 2020)
Idiopathic pulmonary fibrosis (IPF) is an agnogenic, rare, and lethal disease, with high mortality and poor prognosis and a median survival time as short as 3 to 5 years after diagnosis. No effective therapeutic drugs are still not available not only in clinical practice, but also in preclinical phases. To better and deeper understand pulmonary fibrosis will provide more effective strategies for therapy. Mounting evidence suggests that noncoding RNAs (ncRNAs) and their interactions may contribute to lung fibrosis; however, the mechanisms underlying their roles are largely unknown. In this review, we systematically summarized the recent advances regarding the crucial roles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) and crosstalk among them in the development of IPF. The perspective for related genes was well highlighted. In summary, ncRNA and their interactions play a key regulatory part in the progression of IPF and are bound to provide us with new diagnostic and therapeutic targets.

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Impacts of climate warming on maximum aviation payloads - Diandong Ren; Robert E. Dickinson; Rong Fu; Janet F. Bornman; Weidong Guo; Song Yang; Lance M. Leslie (Climate Dynamics, 2019)

Effective inhibition of different Japanese encephalitis virus genotypes by RNA interference targeting two conserved viral gene sequences in vitro and in vivo - Lei Yuan; Xiaojuan Feng; Xuelian Gao; Yu Luo; Chaoyue Liu; Peng Liu; Guolin Yang; Hong Ren; Rong Huang; Yalan Feng; Jian Yang (Virus Genes, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Divergent Selection of Pattern Recognition Receptors in Mammals with Different Ecological Characteristics - Ran Tian; Meixiu Chen; Simin Chai; Xinghua Rong; Bingyao Chen; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2018)

Formation and evolution of Emeishan basalt saprolite in vadose zones of Touzhai landslide source rockmass - Ji-qing Yang; Ze-min Xu; Rui Zhang; Ji-pu Chen; Zhe Ren; Rong-zhang Luo; Xiu-shuo Zhang (Journal of Mountain Science, 2017)

Antioxidant and hyaluronidase inhibitory activities of diverse phenolics in Phyllanthus emblica - Min Xu; Hong-Tao Zhu; Rong-Rong Cheng; Dong Wang; Chong-Ren Yang; Takashi Tanaka; Isao Kouno; Ying-Jun Zhang (Natural Product Research, 2016)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

The trend of soil organic carbon, total nitrogen, and wheat and maize productivity under different long-term fertilizations in the upland fluvo-aquic soil of North China - Wei Gao; Jun Yang; Shun-rong Ren; Liu Hailong (Nutrient Cycling in Agroecosystems, 2015)

Dysfunction of autophagy as the pathological mechanism of motor neuron disease based on a patient-specific disease model - Dan-Jing Yang; Liang Zhu; Jie Ren; Rong-Jie Ma; Hongwen Zhu; Jun Xu (Neuroscience Bulletin, 2015)

Development and evaluation of a loop-mediated isothermal amplification assay for rapid detection of bacterial blight pathogen (Xanthomonas axonopodis pv. dieffenbachiae) in anthurium - Niu Jun-hai; Gao Yue-rong; Yin Jun-mei; Leng Qing-yun; Yang Guang-sui; Wang Cun; Ren Yu (European Journal of Plant Pathology, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

Polycyclic aromatic hydrocarbons associated with total suspended particles and surface soils in Kunming, China: distribution, possible sources, and cancer risks - Xiaoxia Yang; Dong Ren; Wenwen Sun; Xiaoman Li; Bin Huang; Rong Chen; Chan Lin; Xuejun Pan (Environmental Science and Pollution Research, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Differential expression patterns and a novel interaction factor of Damaged DNA Binding Protein 1A (DDB1A) and DDB1B in Arabidopsis thaliana - Pei Hou; Peng-fei Ren; De-er Zeng; Gui-rong Yu; Wei Tang; Xu Zheng; Jian-ping Yang; Yongsheng Liu (Journal of Plant Biology, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

SIRT1 inhibits TNF-α-induced apoptosis of vascular adventitial fibroblasts partly through the deacetylation of FoxO1 - Weirong Wang; Chunfang Yan; Jiye Zhang; Rong Lin; Qinqin Lin; Lina Yang; Feng Ren; Jianfeng Zhang; Meixi Ji; Yanxiang Li (Apoptosis, 2013)

Transient Focal Cerebral Ischemia Induces Long-term Cerebral Vasculature Dysfunction in a Rodent Experimental Stroke Model - Ali Winters; Jessica C. Taylor; Ming Ren; Rong Ma; Ran Liu; Shao-Hua Yang (Translational Stroke Research, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

Preliminary proteomic analysis of circulating polymorphonuclear neutrophils from rabbits experiencing scald injury and Staphylococcus aureus sepsis - Pi-hong Zhang; Li-li Li; Ji-zhang Zeng; Liu-rong Yang; Li-cheng Ren; Peng-fei Liang; Xiao-Yuan Huang (Inflammation Research, 2010)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Liquid-based cytology aids in primary fallopian tube cancer diagnosis - Zhuo Ren; Yun-ping Zhang; Hui-xia Yang; Li-rong Zhu (Journal of Zhejiang University-SCIENCE B, 2009)

Reactions of 3-benzoyl-7-dimethylamino-4-hydroxycoumarin and their potential applications in solution- and solid-phase synthesis - Pei-Yu Kuo; Rong-Ren Chuang; Ding-Yah Yang (Molecular Diversity, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Effect of siRNA on HSV-1 plaque formation and relative expression levels of UL39 mRNA - Ren Zhe; Zhang Mei-Ying; Kaio Kitazato; Nobuyuki Kobayash; Zhu Qin-Chang; Zhang Pei-Zhuo; Yang Zhi-Rong; Wang Yi-Fei (Archives of Virology, 2008)

Enhanced expression of phospholipase C 1 (ZmPLC1) improves drought tolerance in transgenic maize - Chun-Rong Wang; Ai-Fang Yang; Gui-Dong Yue; Qiang Gao; Hai-Ying Yin; Ju-Ren Zhang (Planta, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Knockout of the gene (ste15) encoding a glycosyltransferase and its function in biosynthesis of exopolysaccharide in Streptomyces sp. 139 - Qing-Li Sun; Ling-Yan Wang; Jun-Jie Shan; Rong Jiang; Lian-Hong Guo; Yang Zhang; Ren Zhang; Yuan Li (Archives of Microbiology, 2007)

Characterization of a partial amphiploid between Triticum aestivum cv. Chinese Spring and Thinopyrum intermedium ssp. trichophorum - Yang Zu-Jun; Li Guang-Rong; Chang Zhi-Jian; Zhou Jian-Ping; Ren Zheng-Long (Euphytica, 2006)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

Expression of nucleolus, endosperm storage proteins and disease resistance in an amphiploid between Aegilops tauschii and Secale silvestre - Yang Zu-Jun; Li Guang-Rong; Jiang Hua-Ren; Ren Zheng-Long (Euphytica, 2001)